Single-cell genomic variation induced by mutational processes in cancer - Funnell, Tyler; O’Flanagan, Ciara H.; Williams, Marc J.; McPherson, Andrew; McKinney, Steven; Kabeer, Farhia; Lee, Hakwoo; Salehi, Sohrab; Vázquez-García, Ignacio; Shi, Hongyu; Leventhal, Emily; Masud, Tehmina; et al. (Nature (London), 2022)
How cell-to-cell copy number alterations that underpin genomic instability 1 in human cancers drive genomic and phenotypic variation, and consequently the evolution of cancer 2 , remains understudied. Here, by applying scaled single-cell whole-genome sequencing 3 to wild-type, TP53- deficient and TP53 -deficient; BRCA1 -deficient or TP53 -deficient; BRCA2- deficient mammary epithelial cells (13,818 genomes), and to primary triple-negative breast cancer (TNBC) and high-grade serous ovarian cancer (HGSC) cells (22,057 genomes), we identify three distinct ‘foreground’ mutational patterns that are defined by cell-to-cell structural variation. Cell- and clone-specific high-level amplifications, parallel haplotype-specific copy number alterations and copy number segment length variation (serrate structural variations) had measurable phenotypic and evolutionary consequences. In TNBC and HGSC, clone-specific high-level amplifications in known oncogenes were highly prevalent in tumours bearing fold-back inversions, relative to tumours with homologous recombination deficiency, and were associated with increased clone-to-clone phenotypic variation. Parallel haplotype-specific alterations were also commonly observed, leading to phylogenetic evolutionary diversity and clone-specific mono-allelic expression. Serrate variants were increased in tumours with fold-back inversions and were highly correlated with increased genomic diversity of cellular populations. Together, our findings show that cell-to-cell structural variation contributes to the origins of phenotypic and evolutionary diversity in TNBC and HGSC, and provide insight into the genomic and mutational states of individual cancer cells. Single-cell whole-genome sequencing shows that 'foreground' cell-to-cell structural variation and alterations in copy number are associated with genomic diversity and evolution in triple-negative breast and high-grade serous ovarian cancers.